Defilement Penetrating the Body: A New Understanding of Contamination in Mark 7.15 - Furstenberg, Yair (New Testament studies, 2008)
Mark 7.15, which contrasts two modes of defilement, appears in the gospel as a response to the Pharisaic custom of washing hands before eating. In this article, it is argued that this custom embodies an innovative approach to ritual impurity. Hand washing, which originated, so it is argued, in the Greco-Roman practice, was promoted by the Pharisees along with other purity laws, but stands in contrast to the biblical priestly purity system. In this logion, Jesus rejects the Pharisees' new conception of ritual purity, which was designed to guard the self from impurity. This interpretation offers both a coherent narrative and a plausible understanding of the custom within its historical-social context.